The impact of trifocalization on Philippine education outcomes and the coordination issue - Vicente B. Paqueo; Johanna Marie Astrid A. Sister; Solomon R. Sarne; Marie Louissie Ynez U. Lavega; Aniceto C. Orbeta; Michael Ralph M. Abrigo; Ricxie B. Maddawin (Philippine Institute for Development Studies (PIDS), 2024)
Thirty-two years ago, the First Congressional Commission on Education (EDCOM I) established a trifocalized Philippine Educational and Training System (PETS) to ramp up achievement of the country's educational and training goals. EDCOM I sought to raise the system's performance by transforming the PETS from a centralized Department of Education, Culture and Sports (DECS) into a system with three separate national education agencies, vested with the responsibility and authority to lead on education and training matters. These agencies are the Department for Basic Education (DepEd), the Commission on Higher Education (CHED), and Technical Education and Skills Development Authority (TESDA). Despite well-intentioned reform efforts called for by EDCOM I, the PETS is not performing as well as education and development leaders had hoped for. This state of affairs has led some influential leaders and advisers of EDCOM II to call for a reversal or modification of the current trifocalized PETS. This study seeks to address the above-mentioned concerns and to analyze the proposal to reverse or modify trifocalization. Towards this end, the analysis aims to determine the impact of trifocalization on desired education and skills development outcomes in the Philippines using a combination of quantitative and qualitative methods. This study finds that trifocalization has had no statistically significant impact on education outcomes at conventional confidence levels. The empirical results are consistent with findings drawn from the key informant interviews. Further along, the study discusses why a trifocalized PETS might not work as expected. Given its findings, the report lays some reform ideas that EDCOM II might want to consider and focus on to enable and incentivize the trifocalized system to work better, especially as regards coordination and other issues that key informants interviewed regard as fundamental. Thus, one of these recommendations is the establishment of an independent agency invested with oversight responsibilities and powers to hold DepEd, CHED, and TESDA and other related agencies accountable for their performance in the PETS.
Keywords: 330; Education; Philippines; Basic Education; Governance and Finance; PETS; Higher Education; TVET